The Effect Of Guided Discovery Learning Model Based On Performance Assessment On Students' Science Process Skills In Science Subjects At SMPN 11 Bengkulu Selatan - Boysorongan, Bimon; S, Sukarno; K, Khosi'in (Journal of Innovation in Research, Education and Culture (JIREC), 2024)
The academic problems that arise are: Is there a significant influence in the use of the Guided discovery learning model based on performance assessment on students' science process skills at SMPN 11 South Bengkulu. This research method is a quantitative method. Quantitative research is research that is based on the philosophy of positivism, used to research certain populations or samples, collecting data using research instruments, quantitative/statistical data analysis, with the aim of testing predetermined hypotheses. The research results are as follows: Based on the results of research conducted at SMP Negeri 11 South Bengkulu, the results of data analysis and discussion can be concluded that the experimental hypothesis is accepted. This means that "the guided discovery learning model based on performance assessment has an influence on the science process skills of students in class VIII of SMP Negeri 11 South Bengkulu. This is shown by the results obtained from the t test with the posttest tcount of 4,273 which is greater than the ttable of 2,021 with the conclusion Ho rejected so that H1 is accepted. 102 So the null hypothesis which states there is no (no) influence of the performance assessment-based guided discovery learning model on students' science process skills is rejected and thus the t-test results state that H1 is accepted, namely there is (is) an influence of the model guided discovery learning based on performance assessment of students' science process skills. Keywords: Influence, Model, Guided, Discovery, Learning